First‐in‐human study evaluating safety, pharmacokinetics, and pharmacodynamics of lorundrostat, a novel and highly selective aldosterone synthase inhibitor - Hidetoshi Shimizu; Michael A. Tortorici; Yoshiyasu Ohta; Kei Ogawa; Sheikh Mohammed Ashfaq Rahman; Aya Fujii; Yuki Hiraga; Mizue Kawai; Kanami Sugimoto‐Kawabata; Mattheus (Thijs); Jan Jaap vanLier; Stephen Djedjos; et al. (Wiley, 2024)
Abstract Dysregulation of the mineralocorticoid hormone aldosterone is an increasingly prevalent cause of hypertension. Aldosterone synthase (CYP11B2) shares 93% homology to 11β‐hydroxylase (CYP11B1), which produces cortisol. Lorundrostat, a highly selective inhibitor of CYP11B2, is a potential safe and effective treatment for aldosterone‐dependent, uncontrolled hypertension, including treatment‐resistant hypertension. Lorundrostat showed highly selective inhibition of CYP11B2 in vitro, with 374‐fold selectivity for CYP11B2 vs. CYP11B1. A first‐in‐human study of single ascending doses ranging from 5 to 800 mg and multiple ascending doses ranging from 40 to 360 mg once daily was conducted in healthy participants. After single‐ and multiple‐dose administration, lorundrostat plasma levels peaked 1-3 h after administration with a t1/2 of 10-12 h. Plasma aldosterone decreased up to 40% with single 100‐mg to 200‐mg doses and up to 70% with single 400 to 800‐mg doses. Plasma aldosterone returned to baseline within 16 h after single 100‐mg doses and multiple once‐daily 120‐mg doses. Lorundrostat demonstrated a favorable safety profile in healthy participants. Dose‐ and exposure‐dependent inhibition of renal tubular sodium reabsorption was observed across a clinically relevant dose range with no suppression of basal or cosyntropin‐stimulated cortisol production and only a modest increase in mean serum potassium.